Oceanic redox condition during the late Ediacaran (551–541 Ma), South China. (1st October 2018) - Fan, Haifeng; Wen, Hanjie; Han, Tao; Zhu, Xiangkun; Feng, Lianjun; Chang, Huajin
Abstract: The late Ediacaran (551–541 Ma) oceanic environment could represent a significant preparation for the enrichment of redox sensitive elements during the early Cambrian and even for the evolution of life. However, the marine environment during the late Ediacaran has not been thoroughly characterized to date. To better understand late Ediacaran oceanic redox conditions, we investigated the Fe and S isotopic compositions of cherts from the slope (Yinjiang) and basin (Silikou) sections of the Nanhua basin in South China. The slope (Yinjiang) section is characterized by a wide range of δ 56 FeT values (−0.12‰ to 1.06‰) and by continuously decreasing δ 34 SPy values from 40.4‰ to 4.1‰. The variable δ 56 FeT values in the Yinjiang section primarily reflect the various oxidation degrees of dissolved Fe 2+ in ferruginous seawater. The homogeneous δ 56 FeT signatures (0.02–0.40‰) along the Silikou section and the decreasing trend of δ 56 FeHR values from 0.86‰ to near zero primarily depend on the mixing of Fe 3+ hydroxide/oxide precipitates in a ferruginous water column, possibly followed by partial reduction, the authigenic framboidal pyrite trapped within an intermittent euxinic condition and detrital silicate Fe minerals. A 20–30‰ discrepancy in δ 34 SPy values between the Yinjiang and Silikou sections may be ascribed to the formation of diagenetic pyrites and framboidal pyrites, respectively. Therefore, the continuously decreasing δ 34 SPy values in the Yinjiang and Silikou sections may reflect a significant increase of sulfate diffusion into sediments at the slope location and the enlarged marine sulfate reservoir at the basin location. These new results indicate that the deep water in the Nanhua basin is primarily characterized by a ferruginous condition with intermittent euxinic conditions in the basin location during the late Ediacaran.